Sulfate production by reactive bromine: Implications for the global sulfur and reactive bromine budgets. Issue 13 (11th July 2017) - Chen, Q.; Schmidt, J. A.; Shah, V.; Jaeglé, L.; Sherwen, T.; Alexander, B.
Abstract: Sulfur and reactive bromine (Br y ) play important roles in tropospheric chemistry and the global radiation budget. The oxidation of dissolved SO2 (S(IV)) by HOBr increases sulfate aerosol abundance and may also impact the Br y budget, but is generally not included in global climate and chemistry models. In this study, we implement HOBr + S(IV) reactions into the GEOS‐Chem global chemical transport model and evaluate the global impacts on both sulfur and Br y budgets. Modeled HOBr mixing ratios on the order of 0.1–1.0 parts per trillion (ppt) lead to HOBr + S(IV) contributing to 8% of global sulfate production and up to 45% over some tropical ocean regions with high HOBr mixing ratios (0.6–0.9 ppt). Inclusion of HOBr + S(IV) in the model leads to a global Br y decrease of 50%, initiated by the decrease in bromide recycling in cloud droplets. Observations of HOBr are necessary to better understand the role of HOBr + S(IV) in tropospheric sulfur and Br y cycles. Key Points: Inclusion of HOBr + S(IV) reactions in the model reduces global tropospheric Br y burden by 50% Large fraction of sulfate is produced via HOBr oxidation in the presence of clouds and high HOBr abundance over low‐latitude oceans In‐cloud sulfate production via HOBr oxidation does not necessarily result in less gas‐phase SO2 oxidation